A study on flow characteristics around a hemispherical dome. Issue 1 (February 2021) - Shao, Yu; Qiu, Xiang
Abstract: Large eddy simulation (LES) is used to investigate the unsteady flow around a hemispherical dome. The Reynolds number based on the diameter of the hemisphere is 2.4 × 10 4 . The mean velocity field and fluctuation velocity field were systematically studied. By means of the distribution of mean pressure coefficient, the vulnerable position on the hemispherical dome was found. By means of mean velocity profile, three regions of different properties were divided, and their effects on other creatures and buildings were considered. The probability density function (PDF), joint probability density function (JPDF) and Lumley triangle are further studied. The different intensity of the intermittency of turbulence, the different proportion of ejection (Q2) and sweeping (Q4) events and the anisotropy of Reynolds stress are explained respectively in these three regions.